Identifikasi Miskonsepsi Siswa dengan Menggunakan Metode Certainty of Response Index (CRI) pada Materi Ekosistem Kelas XI MIA MAN 1 Jeneponto - Pebrianto, Ahsanul Qadri; A. Mu’nisa, A. Mu’nisa; Abd. Muis, Abd. Muis (Biology Teaching and Learning, 2020)
Abstract. Identification of StudentsMisconception by Using Certainty of Response Index (CRI) to Ecosystem in Student Class XI MIA on Senior High School. This research aims to know the description of the misconception to grade XI MIA MAN 1 Jeneponto content ecosystem by using the method of Certainty of Responses Index (CRI). This research is descriptive Research. The subject is a student of Class XI and XI MIA3 MIA2 semester odd years lessons 2017/2018 with total students 56 people. Sampling techniques using a purposive sampling technique. Instrument in this study using a diagnostic test multiple choice shaped reasoned that come with the value of the CRI. The results showed that the percentage of level/category/categories on students understanding i.e. understand concepts of 24.11%, understand the concept but less sure of 1.70%, misconception of 37.23% and don't understand the concept in hardness of 36.96%. Percentage of understanding became the most popular category. Keyword: misconception, certainty of response index (CRI), ecosystem